“What should we? What can we?”: Rereading Karl Barth’s self-dialogue on preaching - Nierop, Jantine (Stellenbosch theological journal, 2019)
Over the years there were many small, and even some major shifts of position in the way Karl Barth thought about the sermon. This article shows the internal development in Barth’s homiletic thinking. No position as such is representative of his homiletics. Characteristic is the inner self-dialogue that Barth conducted over many years, specifically on these two questions: What should preachers do? What can they do?